A Brief Introduction to Medical Misadventure - Butler, Petra (Victoria University of Wellington Law Review, 2004)
This article examines the development of medical misadventure law in New Zealand. It discusses the various pieces of legislation impacting on the definition of "medical misadventure" as well as considering the punitive damages cases that are emerging outside ACC against allegedly negligent health professionals and organisations. The author states that the difficulty in devising an appropriate system of accountability lies in the special trust of the doctor patient relationship.